Bovine colostrum and its potential contributions for treatment and prevention of COVID-19 - Duman, Hatice; Karav, Sercan (Frontiers in Immunology, 2023)
Bovine colostrum is the initial milk an animal produces after giving birth particularly in the first few days.Numerous bioactivesubstances found in BC including proteins enzymes growth factors immunoglobulins etc.are beneficial to humanhealth.BC has significant roleto play as part ofhealthy diet, with well-documented health and nutritional advantages forpeopleTherefore the use ofBC and its crucial derivatives in the development of functional food and pharmaceuticalsfortheprevention of several diseases is becoming increasingly popular around the world.A novel coronavirus severeacuterespiratorysyndrome coronavirus 2 was identified as the cause ofcluster of pneumonia cases that is calledCoronavirusDisease 2019 inChina.AfterSARS-CoV-2 virus-related fatality was announced, the illness quickly spreadthroughout China andto other continents, causing a pandemic.Since then numerous studies have been initiated to developsafe and efficienttreatments.To prevent viral infection and potential lingering effects, it is important to investigate alternativetreatments forCOVID-19.Due to its effective bioactive profile and its immunomodulatory roles in biological processes, BCmight beconsidered a promising approach to assist in combating people affected by the SARS-CoV-2 or prevention from thevirus.BC has immunomodulatory effects because to its high concentration of bioactive componentssuch asimmunoglobulinslactoferrin cytokines and growth factorswhich might help control immunological responses, potentiallyfostering a balanced immune response.Furthermore its bioactive components have a potential cross-reactivity against SARSCoV-2 aiding in virus neutralization and its comprehensive food profile also supplies important vitamins, minerals, and aminoacids fostering a healthy immune system.Hencethe possible contributions of BC to the management of COVID-19werereviewed in this articlebased on the most recent researchon the subject.Additionallythe key BC components thatinfluenceimmune system modulation were evaluated.These components may serve aspotential mediators or therapeuticadvantagesinCOVID-19